Marketplace Donations: The Role of Moral Identity Discrepancy and Gender. (April 2020) - Shang, Jen; Reed, Americus; Sargeant, Adrian; Carpenter, Kathryn
A demonstration field experiment in a live-radio fund drive shows that women (but not men) primed with moral traits give about 20% more. The authors test one understudied explanation for this finding: gender differences in how market behavior (e.g., giving and supporting a nonprofit) shrinks moral identity discrepancy (i.e., the gap between actual and ideal moral identity). Field Survey 1 demonstrates the basic effect: the less money women (but not men) have historically given on average to a nonprofit, the larger their moral identity discrepancy. Field Experiment 2 shows a managerial implication of this basic effect: when primed with moral identity, women (but not men) who have supported the nonprofit less frequently in the past are more likely to follow an emailed link to help the nonprofit again. Study 3 tests one possible pathway underpinning this finding: even though giving makes women and men experience similar feelings of encouragement and uplift and similar reinforcement of their moral identity, only women with larger prebehavior moral identity discrepancy consequently shrink this discrepancy.